Negative elevation-dependent warming trend in the Eastern Alps. (19th April 2016) - Tudoroiu, M; Eccel, E; Gioli, B; Gianelle, D; Schume, H; Genesio, L; Miglietta, F
Abstract: Mountain regions and the important ecosystem services they provide are considered to be very vulnerable to the current warming, and recent studies suggest that high-mountain environments experience more rapid changes in temperature than environments at lower elevations. Here we analysed weather records for the period 1975–2010 from the Eastern Italian Alps that show that warming occurred both at high and low elevations, but it was less pronounced at high elevations. This negative elevation–dependent trend was consistent for mean, maximum and minimum air temperature. Global radiation data measured at different elevations, surface energy fluxes measured above an alpine grassland and above a coniferous forest located at comparable elevations for nine consecutive years as well as remote sensing data (MODIS) for cloud cover and aerosol optical depth were analysed to interpret this observation. Increasing global radiation at low elevations turned out to be a potential driver of this negative elevation–dependent warming, but also contributions from land use and land cover changes at high elevations (abandonment of alpine pastures, expansion of secondary forest succession) were taken into account. We emphasise though, that a negative elevation–dependent warming is not universal and that future research and in particular models should not neglect the role of land use changes when determining warming rates over elevation.